Nocardia liver abscess post liver transplantation—A rare presentation. Issue 2 (6th March 2017) - Hanchanale, Pavan; Jain, Mayank; Varghese, Joy; V, Jayanthi; Rela, Mohamed
Abstract: Nocardiosis is usually a disseminated disease seen in immunocompromised individuals. We herein present a rare case of isolated Nocardia liver abscess post liver transplantation. The patient responded well to treatment and is on long‐term antibiotics for Nocardia infection.